2004
DOI: 10.1167/iovs.03-0700
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAP Kinase in Regulation of Cell Migration and Proliferation in Healing Corneal Epithelium

Abstract: Endogenous TGFbeta enhances migration of corneal epithelium during wound healing in mice. The p38MAPK, but not the Smad, cascade plays a major role in promoting cell migration and in suppressing cell proliferation in migrating epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
129
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 46 publications
9
129
0
Order By: Relevance
“…ERK activation is also required in TGF-␤1-induced EMT in pancreatic cancer cells (20) and mammary epithelial cells (21). Activation of p38 MAPK is required in TGF-␤1-induced EMT in mammary epithelial cells (22) and in migration and proliferation of healing corneal epithelium (23). In agreement with these observations, our data also suggest that both p38 MAPK and ERK are required in TGF-␤1-induced EMT in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…ERK activation is also required in TGF-␤1-induced EMT in pancreatic cancer cells (20) and mammary epithelial cells (21). Activation of p38 MAPK is required in TGF-␤1-induced EMT in mammary epithelial cells (22) and in migration and proliferation of healing corneal epithelium (23). In agreement with these observations, our data also suggest that both p38 MAPK and ERK are required in TGF-␤1-induced EMT in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 87%
“…In a normal rat tubular epithelial cell line NRK-52E, Li et al (15) showed that TGF-␤1 induced Smad 2 phosphorylation and resulted in the transformation of epithelial cell into myofibroblast phenotype with the loss of E-cadherin and de novo expression of ␣-SMA and collagens I, III, and IV and that overexpression of Smad 7 resulted in marked inhibition of TGF-␤-induced Smad 2 activation with the prevention of EMT and collagen synthesis. In addition to Smad pathway, Rho A (16,17) and mitogen-activated protein kinases (MAPK) extracellular signal-regulated kinases (ERK) (18 -21), p38 MAPK (22,23), and c-Jun N-terminal kinases (JNK) (24) are involved in TGF-␤1-induced EMT. There is a cross-talk between ERK and Smad 2 (10,25).…”
mentioning
confidence: 99%
“…TGF-b modulates behaviors of several corneal cell types, that is, epithelial cell migration and proliferation and transdifferentiation of keratocytes to myofibroblasts, and also is chemotactic to monocytes/macrophages during wound healing in the cornea as in other tissues. [12][13][14] Blocking signaling mediated by Smad2/3, the cytoplasmic signaling intermediates specific for TGF-b/ activin, is effective in inhibiting injury-induced tissue fibrosis in many tissues, such as skin, kidney, and the lens and retina of the eye. [15][16][17][18][19][20][21][22][23][24][25][26] We have recently revealed that both topical administration of SN50, an inhibitor of NF-kB signal, and adenoviral gene introduction of the Smad7, an inhibitory Smad that blocks Smads2/3, block tissue destruction in an alkali-burned cornea in mice (Saika et al, 2004 24,35 ).…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26][27] We and others have also recently reported that the TGF-b2/ p38MAPK cascade, which is activated in mouse corneal epithelium upon epithelial debridement, is needed for epithelial cell migration and cessation of cell proliferation. 28,29 In mesenchymal cells, p38MAPK is involved in expression of ECM molecules, that is, collagen or fibronectin and cell proliferation. 30,31 While not yet proven, these observations suggest that the p38MAPK pathway might be involved in the pathogenesis of tissue fibrosis, as in PVR.…”
mentioning
confidence: 99%